UNIT 11.11 Electrophysiological Techniques for Studying Synaptic Activity In Vivo. Issue 1 (3rd March 2014) - Jeggo, Ross; Zhao, Fei‐Yue; Spanswick, David
Abstract: Understanding the physiology, pharmacology, and plasticity associated with synaptic function is a key goal of neuroscience research and is fundamental to identifying the processes involved in the development and manifestation of neurological disease. A diverse range of electrophysiological methodologies are used to study synaptic function. Described in this unit is a technique for recording electrical activity from a single component of the central nervous system that is used to investigate pre‐ and post‐synaptic elements of synaptic function. A strength of this technique is that it can be used on live animals, although the effect of anesthesia must be taken into consideration when interpreting the results. This methodology can be employed not only in naïve animals for studying normal physiological synaptic function, but also in a variety of disease models, including transgenic animals, to examine dysfunctional synaptic plasticity associated with neurological pathologies. Curr. Protoc. Pharmacol . 64:11.11.1‐11.11.17. © 2014 by John Wiley & Sons, Inc.